Extreme Environment Sensing Using Femtosecond Laser-Inscribed Fiber Bragg Gratings - Mihailov, Stephen; Grobnic, Dan; Hnatovsky, Cyril; Walker, Robert; Lu, Ping; Coulas, David; Ding, Huimin (Sensors (Basel, Switzerland), 2017)
The femtosecond laser-induced fiber Bragg grating is an effective sensor technology that can be deployed in harsh environments. Depending on the optical fiber chosen and the inscription parameters that are used, devices suitable for high temperature, pressure, ionizing radiation and strain sensor applications are possible. Such devices are appropriate for aerospace or energy production applications where there is a need for components, instrumentation and controls that can function in harsh environments. This paper will present a review of some of the more recent developments in this field.